Voice recognition based wireless home automation system - AlShu'eili, H.; Gupta, G. S.; Mukhopadhyay, S. (2011 4th International Conference on Mechatronics, 2011)
Home Automation industry is growing rapidly; this is fuelled by the need to provide supporting systems for the elderly and the disabled, especially those who live alone. Coupled with this, the world population is confirmed to be getting older. Home automation systems must comply with the household standards and convenience of usage. This paper details the overall design of a wireless home automation system (WHAS) which has been built and implemented. The automation centres on recognition of voice commands and uses low-power RF ZigBee wireless communication modules which are relatively cheap. The home automation system is intended to control all lights and electrical appliances in a home or office using voice commands. The system has been tested and verified. The verification tests included voice recognition response test, indoor ZigBee communication test, and the compression and decompression tests of DPCM (Differential Pulse Code Modulation) speech signals. The tests involved a mix of 35 male and female subjects with different English accents. 35 different voice commands were sent by each person. Thus the test involved sending a total of 1225 commands and 79.8% of these commands were recognised correctly.